Analisis Kepuasan Pelanggan Berbelanja di Pasar Swalayan Maju Bersama terhadap Ketersediaan Produk Sembako - Seriana Seriana; Nico Nico; Vinny Fransiska; Valesia Tjuang; Jesston Jesston (Institut Nalanda, 2024)
The aim of this research is to evaluate the relationship between customer satisfaction at the Maju Bersama Supermarket and the availability of basic food products. Data was obtained through a survey involving 30 supermarket customers. The research method used is simple linear regression. The analysis results show that the availability of basic food products has a limited influence on variations in customer satisfaction; This shows that this factor only has a small influence on the level of customer satisfaction in the supermarket.